2019
DOI: 10.1111/mmi.14233
|View full text |Cite
|
Sign up to set email alerts
|

A two‐component regulatory system VfmIH modulates multiple virulence traits in Dickeya zeae

Abstract: Bacterial pathogen Dickeya zeae strain EC1 produces antibiotics-like phytotoxins called zeamines, which are major virulence determinants encoded by the zms gene cluster. In this study, we identified a zeamine-deficient mutant with a Tn5 insertion in a gene designated as vfmI encoding a two-component system (TCS) sensor histidine kinase (HK), which is accompanied by vfmH encoding a response regulator (RR) at the same genetic locus. Domain analysis shows this TCS is analogous to the VfmIH of D. dadantii , with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(82 citation statements)
references
References 51 publications
2
79
0
Order By: Relevance
“…Furthermore, several regulatory mechanisms associated with c-di-GMP turnover have been implicated in D. zeae virulence from our previous findings; specifically, the two-component system proteins VfmIH and a global transcriptional regulator, SlyA, were reported to regulate some key c-di-GMP turnover enzymes at the transcriptional level, including the primary DGC14945 enzyme (14,16). The AHL quorum sensing signal as well as host-pathogen communication through putrescine signaling were reported to mainly regulate flagellar motility and biofilm formation (17,18).…”
Section: Downloaded Frommentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, several regulatory mechanisms associated with c-di-GMP turnover have been implicated in D. zeae virulence from our previous findings; specifically, the two-component system proteins VfmIH and a global transcriptional regulator, SlyA, were reported to regulate some key c-di-GMP turnover enzymes at the transcriptional level, including the primary DGC14945 enzyme (14,16). The AHL quorum sensing signal as well as host-pathogen communication through putrescine signaling were reported to mainly regulate flagellar motility and biofilm formation (17,18).…”
Section: Downloaded Frommentioning
confidence: 75%
“…In addition, several regulatory mechanisms associated with D. zeae virulence have been uncovered in recent years, including the transcription factors SlyA and Fis (14,15); a two-component regulatory system, VfmHI (16); an acyl-homoserine lactone (AHL)mediated quorum sensing (QS) system (17); a polyamine-mediated host-pathogen communication system (18); and the bacterial second messenger cyclic di-GMP (c-di-GMP) (19). These findings present both a framework and useful clues for dissecting the molecular mechanisms and signaling networks by which D. zeae modulates its physiology and virulence.…”
mentioning
confidence: 99%
“…A study has reported that polygalacturonase inhibiting proteins result in direct inhibition of PG activity or upregulate the defence pathways, in response to fungal infection (Nguema‐Onaet al, 2009). Deletion of either vfmI or vfmH of Dickeya zeae resulted in decreased production of CWDEs and alleviated virulence in host plants, according to Lv et al (2019); the report stated that the necrotizing effect depends on the enzymatic activity. In our study, in the early stage of infection, the pathogen secreted a large number of CWDEs to break through and dissolve the cell wall, and the amount of CWDEs that accumulated within Jz was sufficient to complete the subsequent infection at 4 days postinoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, pGEX-6P-1, the bacterial vector for expressing GST fusion proteins with a PreScission protease site. The expression of this plasmid with the GST label enhances the solubility of the target protein and is widely used in the expression of the target protein, which has not been mentioned the ability of plasmid in killing the bacterial target in a large number of reported literature [ 24 , 47 , 48 , 49 , 50 ]. The screening of bacterial isolate QL-1 ( A. lactucae) capable of degrading DSF has been described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…An Xcc propagate in young stems and leaves through the vascular system, and disease appears as V-shaped chlorotic to necrotic lesions on leaf margins [24]. To determine the effect of the infection time on symptom development, the bacterial strains were inoculated into intact plants of Chinese cabbage and radish.…”
Section: Xcc Expressing Fady Loses Virulence In Plantamentioning
confidence: 99%